Infertility and Risk of Cardiovascular Disease: A Prospective Cohort Study - Farland, Leslie V.; Wang, Yi‐Xin; Gaskins, Audrey J.; Rich‐Edwards, Janet W.; Wang, Siwen; Magnus, Maria Christine; Chavarro, Jorge E.; Rexrode, Kathryn M.; Missmer, Stacey A. (Journal of the American Heart Association, 2023)
Background Certain symptoms associated with infertility are associated with cardiovascular disease, including menstrual cycle irregularity, early menopause, and obesity; however, few studies have investigated the association between infertility and cardiovascular disease risk. Methods and Results Participants in the NHSII (Nurses' Health Study II) who reported infertility (12 months of trying to conceive without success, including women who subsequently conceived) or who were gravid, with no infertility were followed from 1989 until 2017 for development of incident, physician-diagnosed coronary heart disease (CHD) (myocardial infarction, coronary artery bypass grafting, angioplasty, stent) and stroke. Time-varying Cox proportional hazard models were used to calculate hazard ratios (HRs) and 95% CIs and were adjusted a priori for potential confounding variables. Among 103 729 participants, 27.6% reported having ever experienced infertility. Compared with gravid women who had not reported infertility, women with a history of infertility had greater risk of CHD (HR, 1.13 [95% CI, 1.01-1.26]) but not stroke (HR, 0.91 [95% CI, 0.77-1.07]). The association between history of infertility and CHD was strongest among women who reported infertility at an earlier age (HR for infertility first reported at ≤25 years, 1.26 [95% CI, 1.09-1.46]; HR at 26-30 years, 1.08 [95% CI, 0.93-1.25]; HR at >30 years, 0.91 [95% CI, 0.70-1.19]). When we investigated specific infertility diagnoses, elevated risk of CHD was observed among women whose infertility was attributed to an ovulatory disorder (HR, 1.28 [95% CI, 1.05-1.55]) or endometriosis (HR, 1.42 [95% CI, 1.09-1.85]). Conclusions Women with infertility may be at an increased risk of CHD. Risk differed by age at first infertility diagnosis and was restricted to ovulatory- and endometriosis-related infertility.